Serological properties of ordinary and necrotic isolates of Potato virus Y: a case study of PVYN misidentification - Karasev, A.V.; Nikolaeva, O.V.; Hu, X.; Sielaff, Z.; Whitworth, J.; Lorenzen, J.H.; Gray, S.M. (Springer, 2010)
In the course of a multi-year survey of Potato virus Y (PVY) incidence and diversity in the U.S. seed potato crop, an unusual PVY variant was identified in low but significant levels in multiple states. This variant, PVYO-O5, was initially detected by a commercially available PVYN-specific monoclonal antibody, 1F5. This antibody is widely used by U.S. Seed Certification programs to test for PVYN and is one of two antibodies designated by the North American Plant Protection Organization (NAPPO) for pre-shipment testing of tuber lots that are to be transported between countries. Consequently, PVYN positives identified by the 1F5 antibody have triggered quarantine actions, prevented cross-border shipments and impacted trade. Here, we demonstrate by a variety of methods that the PVYO-O5 is a variant within the ordinary PVY strain (PVYO). Specifically, the PVYO-O5 variant likely arose due to a single amino acid substitution within the capsid protein. This variant does not induce vein necrosis in tobacco or tuber necrosis in susceptible varieties of potato. Furthermore, it is identified by RT-PCR based diagnostics as PVYO and it has a typical PVYO genome sequence. We demonstrate that another PVYN specific monoclonal antibody, SASA-N, recognizes an epitope distinct from that recognized by 1F5, and correctly identifies the PVYO-O5 variants as belonging to the PVYO serotype. Since the PVYO-O5 variant is present in many seed producing states and misidentification of PVYO-O5 as PVYN/NTN has clear quarantine implications for export shipments of potato, the limitations of the commercially available monoclonal antibodies should be considered in any certification or phytosanitary testing program